2019
DOI: 10.3390/antiox8060183
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin, A Carotenoid Derived from Phaeodactylum tricornutum Exerts Antiproliferative and Antioxidant Activities In Vitro

Abstract: Microalgae contain a multitude of nutrients and can be grown sustainably. Fucoxanthin, a carotenoid from Phaeodactylum tricornutum, could have beneficial health effects. Therefore, we investigated the anti-inflammatory, antioxidative and antiproliferative effects of fucoxanthin derived from this diatom in vitro. The effects of purified fucoxanthin on metabolic activity were assessed in blood mononuclear cells and different cell lines. In cell lines, caspase 3/7 activity was also analyzed. Nitrogen monoxide rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 54 publications
4
62
2
Order By: Relevance
“…Fucoxanthin has a unique structure compared to other carotenoids like beta-carotene due to its allenic bond, conjugated carbonyl group, 5,6-monoepoxideand carbonyl group. Because of its structure, fucoxanthin has anti-inflammatory, anti-carcinogenic, anti-obesity and anti-diabetic properties [12,[16][17][18][19][20][21]. Therefore, fucoxanthin is supposed to prevent and alleviate several chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Fucoxanthin has a unique structure compared to other carotenoids like beta-carotene due to its allenic bond, conjugated carbonyl group, 5,6-monoepoxideand carbonyl group. Because of its structure, fucoxanthin has anti-inflammatory, anti-carcinogenic, anti-obesity and anti-diabetic properties [12,[16][17][18][19][20][21]. Therefore, fucoxanthin is supposed to prevent and alleviate several chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that fucoxanthin has antioxidant, anti-tumor, anti-inflammatory, and anti-obesity effects [41]. Fucoxanthin extract from PT has been reported to have anti-inflammatory, antioxidant and anti-proliferative effects on blood mononuclear cells and on different cell lines [42]. The fact that OT and PT contain several metabolites known to have effects on human health, such as PUFAs and carotenoids, makes them of interest for disease prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Here, CE showed some cytotoxic effects at high concentrations, increasing cell necrosis at concentrations between 50 µg/mL and 100 µg/mL. Accordingly, a recent study reported a decrease in cell metabolic activity associated with an increase in apoptosis in HepG2 cells treated with 50 µg/mL of fucoxanthin from P. tricornutum [45]. By contrast, TLE showed no toxicity toward HepG2 cells, suggesting that the presence of lipids and/or chlorophylls (chlorophyll a and derivatives such as pheophytin) counteracts the cytotoxicity of carotenoids.…”
Section: Discussionmentioning
confidence: 79%